Experimental study on the transformation of the W70Cu30 anode erosion mode in DC gaseous arcs—better insights into mechanisms of electrode erosion behavior using in situ diagnosis. (5th September 2019) - Cui, Yufei; Niu, Chunping; Wu, Yi; Rong, Mingzhe; Sun, Hao; Niu, Lizhuang; Xiong, Qiancun
Abstract: This research concentrates on the erosion mechanism of the W70 Cu30 anode in DC gaseous arcs. An in situ diagnostic system including the measurement of the anode surface temperature and the fast-imaging of the erosion process was developed. The influence of gas media He, N2, H2, Ar and current, varying from 50 A to 400 A, was investigated. Two erosion modes were observed, namely an evaporation-dominated mode and a splash-dominated mode. The results indicate that the detachment of the splashing droplet is driven by the explosion of surface bubbles, and it is the surface temperature of the anode that determines the size of the surface bubble as well as the splashing erosion rate. Moreover, the prior vaporization of Cu dispersed in the W70 Cu30 anode limits the fusion of the W skeleton but promotes the generation of molten ejections by the explosions of Cu vapor bubbles when the topmost Cu is absent. The large difference between W and Cu in melting and boiling temperatures controls the formation of the molten pool on the W70 Cu30 anode and leads to the transition of the two erosion modes. The experimental results contribute to a fundamental understanding of the interaction between thermal plasmas and materials.